Research trends on biochar-based smart fertilizers as an option for the sustainable agricultural land management: Bibliometric analysis and review - Abiola, Waliou A.; Diogo, Rodrigue V. Cao; Tovihoudji, Pierre G.; Mien, Abdoul K.; Schalla, Andrea (Frontiers in Soil Science, 2023)
Several studies have investigated nutrient-enriched and nutrient poor biochar to improve soil properties, increase nutrient use efficiency and crop productivity. Review articles have presented formulations and production methods of biochar-based fertilizers. They reported nutrient-enriched biochar improves -45ves crop productivity, soil health and preserves the environment. But so far, none of the studies has conceptualized the nutrient-enriched biochar as a biochar-based smart fertilizer or presented the conceptual and intellectual structures and the collaborative networks of authors and countries working on biochar-based smart fertilizers. For the first time, this study has mapped the scientific knowledge generated on the topic and established a solid ground for its innovative progress and research pursuits. A total of 2,779 scientific publications on biochar-based fertilizers were exported from scopus database in August 2022 and were analyzed using bibliometrix software package and the biblioshiny web interface in R version 4.1.3. The results indicated that the papers in our collection cover the period from 2007 to 2022 with a raising number from 2017 to 2021. Almost all documents (99.38%) were co-authored with an average of 6 authors (5.76) per article. The analysis of keywords and the evolution of topics revealed that biochar-based smart fertilizers in relation to organic nutrient sources, soil microbiology and soil sanitation were the most studied topics in the scientific debates. China had more collaboration in the network working on biochar-based fertilizers, while the West African countries belonging to the network have not developed any collaboration so far. This suggests the formulation of research projects that may involve African countries to work with other countries including China, USA, Germany, Australia and Poland. This study is more comprehensive in terms of a global view of the conceptual and intellectual contours and network of actors on biochar-based smart fertilizers. Future research on the topic should be conducted more in the fields under farmers’ conditions and may focus on (i) enrichment of biochar with nutrients from organic sources before its application to the soil, (ii) soil remediation and microbiology in relation to biochar-based fertilizer applications, and (iii) economic profitability of biochar fertilizers for small-scale farmers.